2012
DOI: 10.1590/s1516-89132012000600018
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermentation for the enrichment and extraction of proteins and antioxidant compounds in rice bran by Rhizopus oryzae

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
3
21
1
Order By: Relevance
“…This result is consistent with some researchers who reported an increase in ash content by 30%, 47.8%, and 10.5% [35,38,45]. Increased ash content is thought to result from the growth of hypha and mycelium Rhizopus oryzae on the rice bran.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This result is consistent with some researchers who reported an increase in ash content by 30%, 47.8%, and 10.5% [35,38,45]. Increased ash content is thought to result from the growth of hypha and mycelium Rhizopus oryzae on the rice bran.…”
Section: Resultssupporting
confidence: 92%
“…Protein content in fermented rice bran has an increase of 58.5%. Several authors have reported increase in protein in fermented rice bran by 40%, 53.4%, and 49.3% [35,36,38]. The increase in protein content in this study is higher than previous studies because in this study the rice bran used has particles sizes smaller than 0.42 mm, while in previous research using rice bran with particles sizes between 0.35 and 0.60 mm.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Fermentation using different microbes can increase the levels of bioactive compounds as well as the availability of functional food. For instance, fermentation using Rhizopus oryzae increases the protein content of rice bran (43%); it also increases the levels of phenolic compounds, which have high antioxidant activity, by breaking down lignin in the substrate cell wall [30].…”
Section: Fermentationmentioning
confidence: 99%
“…Furthermore, to inactivate the enzymes in the rice bran that are responsible for rancidity, different stabilization methods are used. Among these, microwave energy offers an alternative energy source for stabilization [30][31][32]. Next, stabilization fractionation is performed.…”
Section: Compositional Improvement As Functional Branmentioning
confidence: 99%